The Most Common Undesired Behaviors from Preschool Teachers’ Perspective in Yanbu Governante - Zaini , Samar Jameel (Dirasat: Educational Sciences, 2024)
Objectives: The study aimed to identify the most common undesirable behaviors in kindergarten children from the point of view of kindergarten teachers in Yanbu Governorate, Saudi Arabia. In addition to knowing the effect of teachers’ years of experience, academic specialization, and attending training courses in behavior management on teachers’ assessment of common undesirable behaviors. Methods: A comparative descriptive approach was used, where the researcher developed a scale for undesirable behaviors in kindergarten children, consisting of (61) items, and applied it to a sample of (203) female teachers. Results: The results showed that the most common undesirable behaviors are hyperactivity and impulsivity, inattention, and self-stimulation. A statistically significant difference regarding the degree of prevalence of undesirable behaviors attributed to the variable of academic specialization in favor of teachers specializing in the field of early childhood education, and according to the variable years of experience towards teachers whose experience is less than five years, and according to the variable of attending training courses in favor of teachers who attended training in behavior management. Conclusions: The most common undesirable behaviors are hyperactive and impulsive behaviors, poor attention, and self-stimulation. Therefore, the study recommends focusing on training kindergarten teachers to deal with hyperactive and impulsive behaviors, designing activities that attract children’s attention, in addition to providing training on effective classroom management, and the characteristics of children’s development to help teachers distinguish between undesirable behaviors and the child’s natural developmental characteristics.